An Analysis of the Moisture Content of Internal Insulation Structures According to the Installation of Vapor Retarder Based on Meteorological Data by Region: Focused on South Korea - Jang, Hyang-In; Kim, Kyung-Soo; Hong, Soung-Wook; Choi, Chang-Ho (International Journal of Engineering and Technology, 2019)
In South Korea, concealed condensation evaluations are carried out based on the â€˜condensation prevention design standards for apartment housing,â€™ which only consider evaluations of the surface condensation of a structure (temperature). In addition, the evaluations consider only the monthly average outdoor temperature upon classifying outdoor conditions into three regions, which will not yield accurate results in terms of an assessment of condensation. Furthermore, cases of condensation and reverse condensation occur frequently due to a lack of regulations concerning the installation of vapor retarding layers within internal insulation structures where multiple occurrences of condensation may develop. To analyze levels of condensation according to the meteorological conditions of each region regarding internal insulation walls according to the presence or absence of vapor retarding layers, this study collected meteorological data from 20 different regions in South Korea, and undertook evaluations using simulations. The conclusions of this research are as follows. 1) The results of extracting meteorological data factors to undertake evaluations of concealed condensation indicated that temperature, relative humidity, total solar radiation, diffuse sky radiation, wind speed, wind direction, and precipitation have relevance. 2) The results of concealed condensation simulation evaluations using the meteorological data of 20 regions of South Korea presented differences according to the meteorological characteristics of each region, with concealed condensation found to have a more sensitive effect on a structure in regions closer to the coast. 3) For internal insulation structures installed with vapor retarding layers, the incidence of concealed condensation was high in coastal regions; in the case of internal insulation structures that were not installed with vapor retarding layers, the incidence of concealed condensation was low in Southern regions where high temperatures were present. 4) The results of a comparative analysis indicated that across all regions, the incidence of concealed condensation was lowest in internal insulation structures installed with vapor retarding layers. Â Â